Survey of Physical Conditions of Futsal Extracurricular Students at SMAN 10 Pekanbaru: Survei Kondisi Fisik Siswa Ekstrakurikuler Futsaldi SMAN 10 Pekanbaru - Rezki Adrian; Merlina Sari (Badnur Medisa Group, 2022)
This study aims to determine the physical condition of futsal extracurricular students at SMAN 10 Pekanbaru. The samples in this study were futsal extracurricular students at SMAN 10 Pekanbaru, totaling 15 people. This type of research is quantitative descriptive research, the instruments used consist of a leg dynamometer test, vertical jump, a 50-meter running test, a shuttle run test, and a 15-minute running test. Based on data processing carried out with the statistical system, there were 13 students who received less categories with a percentage (86.67%), while there were enough categories with 2 people with percentages (13.33%). Thus, the average score of futsal extracurricular students at SMAN 10 Pekanbaru is 2.75 which is classified as at intervals of 2.0 – 3.9. Thus, it can be said that the survey of the physical condition of futsal extracurricular students at SMAN 10 Pekanbaru is classified as lacking.